A Degree that Enables Basic Education Teachers to have the Necessary Skills to Use Problem Solving Method (A field study by a sample of teachers from schools in Lattakia city) - قاسم رهام (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The aim of the current research is to determine the degree to which teachers of the basic education stage have the necessary skills to use the problem-solving method from their point of view, in addition to knowing the difference in the degree of their mastery of these skills depending on the variables (educational qualification, duration of service, type of secondary certificate), and to achieve the previous goals designed.The researcher has a questionnaire consisting of (25) items distributed on three main axes that include the skills necessary to use the problem-solving method. The sample of the research consisted of (774) male and female teachers from basic education teachers in the city of Lattakia. The results showed that the degree to which teachers were able to use the skills needed to use the problem-solving method came at a high level for the questionnaire as a whole, and there were no statistically significant differences between the averages of their responses about the degree of their mastery of these skills with respect to the questionnaire as a whole and in both skills (defining the problem, choosing the most appropriate solution) according to the three variables, while there were statistically significant differences in the degree of their ability to (reaching a solution to the problem) according to the variables of the educational qualification and the period of service for the benefit of class teachers and those with 10 years or less experience, While there were no differences in the degree of their mastery of this skill according to the variable of the type of secondary certificate.